Changes in German Mental Health Care by Implementing a Global Treatment Budget—A Mixed-Method Process Evaluation Study - Schwarz, Julian; Galbusera, Laura; Bechdolf, Andreas; Birker, Thomas; Deister, Arno; Duve, Annette; Heiser, Philip; Hojes, Kerit; Indefrey, Sonja; Johne, Jakob; Rehr, Burkhard; Rout, Sandeep; et al. (Frontiers in Psychiatry, 2020)
Background: Internationally, there is a broad spectrum of outreach and integrative care models, whereas acute psychiatric treatment in Germany is still mostly provided in inpatient settings. To overcome this, a new legal framework (§64b Social Code V) has been introduced, promoting „Flexible and Integrative Treatment“ (FIT64b) models, based on a “Global Treatment Budget” (GTB) financing approach. Although each of the recent 23 adopters has implemented the framework according to local needs and concepts, prior research could identify FIT64b specific components. Based on this, our paper aims to examine the implementation process and underpinning change mechanisms of GTB-based FIT64b models from a staff, service user and caregiver perspective. Method: 31 focus groups and 15 semi-structured interviews were conducted with hospital staff (n = 138), service users (n = 63) and caregivers (n = 35) in 10 psychiatric hospitals implementing FIT64b. Using qualitative analysis, we identified 5 core themes describing the implementation process, which were theoretically modelled into a logical diagram. The core mechanisms of change were thus identified across themes. Additional structural and semi-quantitative performance data was collected from all study departments. Results: The qualitative analysis showed that the shift from a daily- and performance-based payment to a lump-sum GTB and the shift of resources from in- to outpatient settings were of crucial importance for the process of change. Saved budget shares could be reinvested to integrate in-, out- and day-patient units and to set up outreach home care. Clinicians reported feeling relieved by the increase of treatment options. They also emphasized a stronger relationship with and a better understanding of service users and a simplification of bureaucracy. Finally, service users and caregivers experienced higher need-adaptedness of treatment, a feeling of deeper understanding and safety, and the possibility to maintain everyday life during treatment. Finally, two FIT64b implementation prototypes were classified according to the semi-quantitative performance data. Conclusion: Based on the results, we developed 3 core mechanisms of change of FIT64b models: 1. Need-adaptedness and flexibility; 2. Continuity of care; 3. Maintaining everyday life. Our findings outline and emphasize the potentials a GTB approach may have for improving psychiatric hospital services.